2011
DOI: 10.2478/s13386-011-0035-4
|View full text |Cite
|
Sign up to set email alerts
|

The E1’ center in natural quartz: Its formation and applications to dating and provenance researches

Abstract: Quartz is one of the minerals useful for electron spin resonance (ESR) dating. The E 1 ' center is one of well-known paramagnetic defects in crystalline quartz. This center has a unique feature; its intensity increases on heating. An electronic process to explain this increase was found to be controlled not only by the number of oxygen vacancies, which are the precursors, but also by the number of Al hole centers, which depend on the previous radiation dose and on the Al concentration. The maximum intensity on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The E ′ (the •Si≡O moiety) centres are the most frequent defects in quartz apart from Al centres and can occur in different stages depending on thermal stability and sensibility to irradiation (Griscom, 1985). The most common E ′ 1 centre can be formed by various irradiations involving alpha particles, electron beams, neutrons, gamma- and X-rays, and has been used as palaeo-dosimeters and geochronometers due to its high thermal stability (> 550°C) (Moiseev, 1985; Toyoda, 2011, 2016). In addition, the E ′ 1 centre in nature, induced by diverse radiation sources from U/Th-bearing rocks/fluids to potassic alteration, can be used as an indicator for the formation of uranium deposits when the dominant source of radiation is uranium (Pan et al , 2006; Botis et al , 2006, 2008; Cerin et al , 2017).…”
Section: Point Defects In Quartzmentioning
confidence: 99%
“…The E ′ (the •Si≡O moiety) centres are the most frequent defects in quartz apart from Al centres and can occur in different stages depending on thermal stability and sensibility to irradiation (Griscom, 1985). The most common E ′ 1 centre can be formed by various irradiations involving alpha particles, electron beams, neutrons, gamma- and X-rays, and has been used as palaeo-dosimeters and geochronometers due to its high thermal stability (> 550°C) (Moiseev, 1985; Toyoda, 2011, 2016). In addition, the E ′ 1 centre in nature, induced by diverse radiation sources from U/Th-bearing rocks/fluids to potassic alteration, can be used as an indicator for the formation of uranium deposits when the dominant source of radiation is uranium (Pan et al , 2006; Botis et al , 2006, 2008; Cerin et al , 2017).…”
Section: Point Defects In Quartzmentioning
confidence: 99%
“…Based on above studies, Toyoda et al (2016) proposed that since the quartz heat-treated E 1 ' centre is correlated with the age of quartz, it can be an effective indicator of age in source rocks. Therefore, the heat-treated E 1 ' centre of quartz have been considered as a new powerful tool for provenance study (Ono et al, 1998;Attanasio et al, 2000;Duttine et al, 2002;Toyoda and Naruse, 2002;Crook et al, 2002;Nagashima et al, 2007Nagashima et al, , 2011Sun et al, , 2008Sun et al, , 2013Toyoda, 2011;Yamamoto et al, 2013;Shimada et al, 2013;Tissoux et al, 2015;Toyoda et al, 2016;Shimada et al, 2016;Satio et al, 2017). In order to detect the correlation between the heat-treated E 1 ' signal intensity of fluvial sedimentary quartz and its source rock age, we compared the ESR signal intensities for the fluvial sediments and source rocks when heated at 300°C and 330°C, respectively (Fig.…”
Section: Relationship Of Esr Signal Intensity Of Quartz Between Sedim...mentioning
confidence: 99%
“…However, more recent studies indicated that the ESR signal intensity of heat-treated E 1 ' centre, after gammaray irradiation to 2.5 kGy followed by heating at 300°C for 15 min, was correlated to the age of quartz (Ono et al, 1998;Toyoda and Hattori, 2000;Toyoda and Naruse, 2002;Sun et al, 2007). Thus, on the basis of the correlation between the quartz ESR intensity and its source rock age, the heat-treated E 1 ' centre could be used to trace sediment provenance (Attanasio et al, 2000;Nagashima et al, 2007Nagashima et al, , 2011Sun et al, 2008Sun et al, , 2013Toyoda, 2011;Yamamoto et al, 2013;Shimada et al, 2013Shimada et al, , 2016Tissoux et al, 2015;Toyoda et al, 2016, Satio et al, 2017. Previous studies have mainly focused on the heattreated E 1 ' centre of aeolian sediment, while studies on fluvial and lacustrine sediments are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Studies about sources provenance where previously conducted, mainly based on the E1 0 ESR center (Toyoda and Ikeya, 1991;Toyoda, 2011;Shimada et al, 2013) and the radiosensitive Al, Ti and Ge centre (Duttine et al, 2002). In this paper, two kind of data were used for sources discrimination: the radionuclides content in the surrounding sediment, involved in the annual dose (da) determination, and the ESR parameters of quartz grain, involved in the Equivalent Dose (De) determination (Al and Ti centres).…”
Section: Introductionmentioning
confidence: 99%